Pancreatic impairment and Igf2 hypermethylation induced by developmental exposure to bisphenol A can be counteracted by maternal folate supplementation. Issue 7 (6th February 2017) - Mao, Zhenxing; Xia, Wei; Huo, Wenqian; Zheng, Tongzhang; Bassig, Bryan A.; Chang, Huailong; Chen, Tian; Li, Feie; Pan, Yunxin; Peng, Yang; Li, Yuanyuan; Xu, Shunqing
Abstract: Increasing evidence indicates that bisphenol A (BPA), a widely manufactured environmental pollutant, can induce changes in DNA methylation paatterns, which is a potential mechanism linking this environmental exposure to disease development. We investigated the influence of developmental exposure to BPA on pancreatic DNA methylation patterns and whether maternal folate supplementation can modify the epigenetic status and pancreatic impairment induced by BPA. Our results showed that maternal dietary folate supplementation in rats exposed to BPA counteracted the observed BPA‐induced pancreatic impairments in the offspring, which included disrupted insulin secretion and glucose intolerance, and impaired morphology and ultrastructure of β cells. Moreover, these pancreatic dysfunctions were shown to be associated with low expression and DNA hypermethylation of insulin‐like growth factor‐2 ( Igf2 ) in islets induced by exposure to BPA during the developmental period. Importantly, maternal dietary folate supplementation was demonstrated to negate this Igf2 DNA hypermethylation in the offspring, which was consistent with the upregulation of Igf2 expression. Overall, our results suggest that early developmental exposure to BPA alters the DNA methylation of Igf2, that these altered methylation patterns are associated with impaired β‐cell function in the offspring and that these effects can be counteracted by maternal folate supplementation. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Perinatal BPA exposure can induced epigenetic modification in offspring islet. Maternal folate supplementation can ameliorate perinatal BPA‐induced glucose intolerance and β‐cell dysfunction in the offspring. Perinatal BPA exposure induced DNA hypermethylation of Igf2 in offspring islets which can be counteracted by maternal folate supplementation. The changes of epigenetics in islet may contribute to the protection.